Recovery of mutans streptococci on MSB, SB-20 and SB-20M agar media - Saravia, Marta Estela; Nelson-Filho, Paulo; Silva, Raquel Assed Bezerra; De Rossi, Andiara; Faria, Gisele [UNESP]; Silva, Léa Assed Bezerra; Emilson, Claes-Göran (Elsevier, 2013)
Objective: The recovery of mutans streptococci in saliva and dental biofilm samples depends, in part, on the culture medium used. In this study, we compared (i) the culture media Sucrose-Bacitracin agar (SB-20), Modified SB-20 (SB-20M) and Mitis Salivarius Bacitracin agar (MSB) in the count of colony forming units (cfu) of mutans streptococci and (ii) in the morphological and biochemical differentiation between Streptococcus mutans and Streptococcus sobrinus. Design: Samples of non-stimulated saliva from 20 children were plated on SB-20, SB-20M and MSB, and incubated in microaerophilia at 37 °C for 72 h. Identification of microorganisms was based on analysis of colony morphology under stereomicroscopy. The biochemical identification of colonies was done by biochemical tests using sugar fermentation, resistance to bacitracin and hydrogen peroxide production. Results: There was no significant difference (p > 0.05) in the number of cfu of mutans streptococci recovered on SB-20 and SB-20M agar. Comparing the media, SB-20 and SB-20M yielded a larger number of mutans streptococci colonies (p < 0.05) and were more effective than MSB in the identification of S. sobrinus (p < 0.05), but not of S. mutans (p > 0.05). Conclusion: There was no significant difference between SB-20 and SB-20M culture media in the count of mutans streptococci, demonstrating that the replacement of sucrose by coarse granular cane sugar did not alter the efficacy of the medium. Compared with MSB, SB-20 and SB-20M allowed counting a larger number of mutans streptococci colonies and a more effective morphological identification of S. sobrinus. © 2012 Elsevier Ltd.
Keywords: Selective culture media; Streptococcus mutans; Streptococcus sobrinus; agar; antiinfective agent; bacitracin; sucrose; antibiotic resistance; bacterial load; bacterium identification; biofilm; child; classification; comparative study; culture medium; fermentation; human; isolation and purification; metabolism; microbiological examination; microbiology; preschool child; saliva; Agar; Anti-Bacterial Agents; Bacitracin; Bacterial Load; Bacterial Typing Techniques; Bacteriological Techniques; Biofilms; Child; Child, Preschool; Culture Media; Drug Resistance, Bacterial; Fermentation; Humans; Saliva; Sucrose; Streptococcus